Behavior and design-oriented model for elliptical FRP-confined concrete under axial compression. (15th December 2021) - Chen, Guipeng; Wang, Yanlei; Yu, Tao; Wan, Baolin; Zhang, Bing; Liu, Qing
Highlights: Elliptical FRP-confined high-strength concrete stub columns are axially loaded. Increasing aspect ratio always has adverse effect on behavior of inner concrete. Typical stress–strain curves of confined concrete are categorized into four types. Threshold for sufficient confinement of elliptical FRP-confined concrete is given. A design-oriented model for elliptical FRP-confined concrete is developed. Abstract: Elliptical fiber-reinforced polymer (FRP)-confined concrete members have gained increasing attention due to their aesthetical characteristics and structural efficiency. This paper investigated the behavior of 24 elliptical FRP-confined concrete stub columns under axial compression. Effects of the amount of FRP confinement, the cross-sectional aspect ratio, and the use of high-strength concrete were discussed. The test results indicated that the stress and strain capacities of the confined concrete were enhanced with the increasing amount of FRP confinement. By contrast, the increasing sectional aspect ratio and the use of high-strength concrete had an adverse effect on the inner concrete's axial behavior due to the increasingly non-uniform distribution of FRP confining pressure. In general, the typical stress–strain curves of elliptical FRP-confined concrete were categorized into four types. Furthermore, using the concept of equivalent diameter, the threshold for sufficient confinement of elliptical FRP-confined concrete was determined by the equivalent confinement stiffness ratio to ensure an overall ascending behavior. After addressing some key issues, a design-oriented model for elliptical FRP-confined concrete with a relatively wider range of concrete strength (from 32.6 to 72.4 MPa) was developed herein with more satisfactory accuracy than existing models. This model with a simple form could be naturally reduced to a widely accepted model for FRP-confined concrete with circular sections.